MONITORING THE SHIFT OF RAINFED LINE OF 250 mm OVER IRAQ - Y. K. Al-Timimi; F. Y. Baktash (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was aimed to analyze the annual rainfall and study the changes in the borders of rainfed regions in Iraq. Monthly rainfall data for 39 meteorological stations affiliated with the Iraqi Ministry of Transportation /Iraqi Meteorological Organization and Seismology have been used. These data represent a Long-term Climate Records from January 1980 to December 2020 have been used to calculate the mean annual rainfall in Iraq over the 41 years. The resultes showed significant spatial and temporal variability in the annual mean rainfall, with higher values in the northern areas of Iraq and lower values in the southern regions. It was examined the succession of the rainfed line at 250mm. The results indicated that there have been clear changes in the rained line of 250 mm during the four different decades (1980–1990, 1990–2000, 2000–2010, and 2010–2020). Iraq was located between the 100 mm rain line at the south and the 1277 mm rain line at the far northeast. Iraq became located between the 100-1000 mm rain line. During the four time periods, the area of the rainfed agriculture region, which depends on a 250 mm rainfall line, amounted to 20.38%, 20.17%, 14.91%, and 17.01%. In general, the area of the region decreased in the southeast and north during the first, second, and third time periods and then expanded slightly during the fourth time period.